2019
DOI: 10.4102/sajhivmed.v20i1.855
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about male circumcision and perception of risk for HIV among youth in Harare, Zimbabwe

Abstract: Background Male circumcision will require high uptake among previously non-circumcising countries to realise the impact of circumcising in preventing HIV. Little is known about whether youths are knowledgeable about male circumcision and its relationship with HIV prevention and their perception of risk of HIV infection. Objective This article aimed to ascertain youth’s knowledge about male circumcision and perception of risk of HIV infection. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…This is consistent with the previous study that found that 66 % % of unmarried and 36% of unmarried had an uptake of MMC [46]. However, being unmarried was associated with the highest odds of having ever tested for HIV among men in Zambia in this study, this supports prior studies that found that being married was correlated with higher knowledge of HIV prevention among men [22,25,44]. It is also possible that married men or those in long-term relationships may be more likely to have routine check-ups or visits to healthcare providers where they can discuss and receive information about sexual health, including HIV testing compared to those who are not married.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the previous study that found that 66 % % of unmarried and 36% of unmarried had an uptake of MMC [46]. However, being unmarried was associated with the highest odds of having ever tested for HIV among men in Zambia in this study, this supports prior studies that found that being married was correlated with higher knowledge of HIV prevention among men [22,25,44]. It is also possible that married men or those in long-term relationships may be more likely to have routine check-ups or visits to healthcare providers where they can discuss and receive information about sexual health, including HIV testing compared to those who are not married.…”
Section: Discussionsupporting
confidence: 92%
“…The beliefs and values rooted in religious perspectives on sexuality could serve as potential mechanisms supporting HIV testing for men in Zambia. Plausibly, the association between low perception of risk of HIV infection and religion could be attributed to their teachings on nurturing religious experiences and strong synergies encouraged among members [44]. Socialization of congregants towards more frequent and overlapping interactions can discourage members' involvement in risky sexual behaviors and hence impact on their perception of risk of HIV infection, and the benefits of MMC.…”
Section: Discussionmentioning
confidence: 99%
“…The improved awareness programs in the lower level of learning such as primary and secondary school levels could have played a significant role in providing knowledge on the benefits of circumcision among the study participants. The findings from this study agree with the results from the previous study among college students in Eswatini and Zimbabwe where all the participants perceived risk reduction in HIV contraction following medical circumcision [ 13 , 18 ]. However, this HIV risk reduction perception is extremely higher than the one reported among university students in Nigeria were only 38% were aware of the role of medical circumcision in the reduction of HIV acquisition [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another factor was level of formal education. Secondary and higher education were signi cantly associated with uptake of VMMC similar to ndings elsewhere in Africa [7,31,32]. It is therefore imperative to implement VMMC interventions targeting out of school youths with higher levels of school drop-outs such as boda-boda riders.…”
Section: Discussionsupporting
confidence: 60%